Biomaterials functionalized with nanoclusters of integrin‐ and syndecan‐binding ligands improve cell adhesion and mechanosensing under shear flow conditions. Issue 3 (29th June 2020) - Karimi, Fatemeh; Thombare, Varsha Jagannath; Hutton, Craig A.; O'Connor, Andrea J.; Qiao, Greg G.; Heath, Daniel E.
Abstract: We have engineered biomaterials that display nanoclusters of ligands that bind both integrin and syndecan‐4 cell receptors. These surfaces regulate cell behaviors under static conditions including adhesion, spreading, actin stress fiber formation, and migration. The syndecan‐4 receptors are also critical mediators of cellular mechanotransduction. In this contribution we assess whether this novel class of materials can regulate the response of cells to applied mechanical stimulation, using the shear stress imparted by laminar fluid flow as a model stimulus. Specifically, we assess endothelial cell detachment due to flow, cell alignment due to flow, and cell adhesion from the flowing fluid. A high degree of cell retention was observed on surfaces containing integrin‐binding ligands or a mixed population of integrin‐ and syndecan‐binding ligands. However, the presence of both ligand types was necessary for the cells to align in the direction of flow. These results imply that integrin engagement is necessary for adhesion strength, but engagement of both receptor types aids in appropriate mechanotransduction. Additionally, it was found that surfaces functionalized with both ligand types were able to scavenge a larger number of cells from flow, and to do so at a faster rate, compared to surfaces functionalized with only integrin‐ or syndecan‐binding ligands. These results show that interfaces functionalized with both integrin‐ and syndecan‐binding ligands regulate a significant range of biophysical cell behaviors in response to shear stress. Abstract :